Expressions of disapproval in a virtual professional forum: a study on (im)politeness and facework - Ana Larissa Oliveira (Calidoscópio, 2023)
This study focuses on the expressions of disapproval and their follow-up responses found in a forum of teaching development held at a federal university in Brazil. The framework of facework (Goffman, 1967; Brown and Levinson, 1987; Leech, 2014), and relational work (Garfinkel, 1964; Locher, 2004; Spencer-Oatey, 2005; Haugh, 2014; Culpeper and Tantucci, 2021) support the research. Of relevance to this study are the strategies employed to enhance reciprocity and to display compliance with pre-established social norms of forum participation (Landone, 2021; Orsini-Jones and Lee, 2018). We hypothesize that, in the face of a threat, in this case, an expression of disapproval, intersectional and interactional politeness strategies are applied so that professional images are jointly constructed and reaffirmed. To categorize the data, we manually analyzed the expressions of disapproval employing the categories adapted from Schaefer (1982, p. 14-15) and Traverso (2009). The results show that the expressions of disapproval were mitigated to promote face protection and to assure reciprocity. As for the follow-up responses, they focused on pursuing professional ethics, particularly related to principles of guidance, and solidarity. Altogether, the strategies identified lessened the emergence of conflict while curbing genuine debate, therefore diverging from the original objectives of a forum.